Repair, by-pass and replacement in the urinary tract. - Coetzee, Theunis; Coetzee, Theunis (Department of Obstetrics and Gynaecology, 2017)
The subject matter of this thesis might appear to consist of eleven separate essays. These have been grouped under the headings repair, by-pass and replacement. However, it is believed that the same theme might be apparent throughout, based chiefly on the following considerations: a. Retrospective survey of case notes forms no part of this thesis. It is a record of personal observation of every patient mentioned. The evolution of ideas and techniques is the result of close observation of the progress of these patients, sometimes modified after a careful evaluation of the observations of other workers as reported in the medical literatures b. At no time was a consideration of the patient, as an integrated whole, and the evaluation of the entire urinary tract, sacrificed in the approach to a study of the more localized pathology. It is firmly believed that such an omission will be to the detriment of the patient. Whatever part of the urinary tract is involved, therefore, the approach to the problem remains fundamentally the same. c. In the management of these cases there has always been the closest cooperation between the urological surgeon and his colleague in gynaecology. This has always ensured an objective and critical check in all decisions regarding management of cases. Such a close combination of two disciplines has promoted further uniformity of approach to problems varying in detail. Therefore, although the subject matter has been subdivided into eleven sections, the problem in them all remains basically the same and there is considerable overlap between the sections. only to facilitate systematic discussion.